SEARCH OF TUBERCULOSIS SUSCEPTIBILITY GENES USING THE RESULTS OF GENOME-WIDE ASSOCIATION STUDY OF CROHN’S DISEASE - A. A. Rudko; M. B. Freidin; Ye. Yu. Bragina; A. R. An; V. P. Puzyryov (Бюллетень сибирской медицины)
Crohn’s disease (CD) and tuberculosis (TB) share several mechanisms of pathogenesis, and this suggests they also have common genetic susceptibility factors. To test this hypothesis, we performed the analysis of association between TB and polymorphisms of genes associated with CD, according to the results of genome-wide association studies, in Russians from Tomsk and indigenous people from Tuva. For the first time, The rs2872507 (ORMDL3), rs3810936 (TNFSF15), rs10192702 (ATG16L1), rs9286879 (1q24.3), rs10507523 (13q14.11) polymorphisms were found to be associated with TB in Russians. The rs1407308 (TNFSF15) and rs1736135 (21q21.1) were associated with the disease in Tuvinians. The associations found are likely due to the functional role of the relevant proteins and their pathogenetic influence on the immune reaction underlying tuberculosis infection. Overall, the study of polymorphisms associated with CD allowed us to identify new candidate genes for TB.